Methylparaben induces hepatic glycolipid metabolism disorder by activating the IRE1α-XBP1 signaling pathway in male mice - Haining Du; Jiaxin Li; Xiangjuan Wei; Daqian Yang; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Yuxia Zhang; Xiaoyan Li; Ning Gu (Environment International, 2024)
Methylparaben (MP), a preservative widely used in daily supplies, exists in both the environment and the human body. However, the potential health risks posed by MP remain unclear. This study aimed to unravel the mechanisms by which MP disrupts glucose and lipid homeostasis. For this, we administered MP to mice and observed changes in glucose and lipid metabolism. MP exposure led to hyperglycemia, hyperlipidemia, visceral organ injury, and hepatic lipid accumulation. RNA sequencing results from mice livers indicated a close association between MP exposure and endoplasmic reticulum (ER) stress, inflammatory response, and glucose and lipid homeostasis. Western blotting and quantitative reverse transcription–polymerase chain reaction revealed that MP activated ER stress, particularly the inositol-requiring enzyme 1 (IRE1)/X-box binding protein 1 (XBP1) pathway, which further promoted the activation of the nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. The activation of these pathways phosphorylated insulin receptor substrate-1 (IRS1) (ser 307), resulting in decreased phosphorylation of protein kinase B (Akt) (ser 473), leading to insulin resistance. Additionally, MP exposure promoted lipogenesis through ER stress. To explore potential remedies, we administered the ER stress inhibitor 4-phenylbutyric acid (4-PBA) and the IRE1α-XBP1 pathway inhibitor toyocamycin to mice, both of which protected against metabolic disorders and organ injury caused by MP. These findings suggest that MP induces disruptions in glucose and lipid metabolism through ER stress, primarily through the IRE1α-XBP1 pathway.